Infracciones, penas y multas por maltrato animal en América Latina - Ortega Peñafiel, Sebastián Andrés (2021)
Our society suffers different types of violence, among which we find the mistreatment of domestic animals, facts that by their nature have remained a long time in impunity for various aspects such as: considering animals as things lacking legal protection, enforcement of pecuniary penalties and light custodial penalties for the perpetrators of the various behaviors that range from abandonment to the death of the animal. The methodology to be used is the bibliographic review in recent and documentary publications with the different legal norms of each country referring to the subject. The method used is descriptive - argumentative, the collection of information starts with the use of databases, Radalyc, Proquest and Scopus. Results obtained are shown in the table of the analysis of infractions, sanctions and penalties in Latin America for animal abuse. With the conclusions it can be shown that, in Latin America animal abuse is one of the greatest problems facing our society, animals must be protected as subjects of rights, respecting their condition of vulnerability. Discussion, to prevent and eradicate animal abuse, not only sanctioning norms are enough, education from home, educational centers and society is important.